2012
DOI: 10.1016/j.ins.2011.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Tabu assisted guided local search approaches for freight service network design

Abstract: The service network design problem (SNDP) is a core problem in freight transportation. It involves the determination of the most cost-effective transportation network and the characteristics of the corresponding services, subject to various constraints. The scale of the problem in real-world applications is usually very large, especially when the network contains both the geographical information and the temporal constraints which are necessary for modelling multiple service-classes and dynamic events. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Since the majority of previous research efforts for M-Determ and M-Stoch1 have been focusing on metaheuristic approaches, for example tabu search (Pedersen et al, 2009) and guided local search (Bai et al, 2012) for M-Determ and variable neighbourhood search with fast approximations (Hoff et al, 2010) for MStoch1, we expect that similar approaches would also be suitable for M-Stoch2 although M-Stoch2 is much harder due to the additional rerouting variables.…”
Section: Solution Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the majority of previous research efforts for M-Determ and M-Stoch1 have been focusing on metaheuristic approaches, for example tabu search (Pedersen et al, 2009) and guided local search (Bai et al, 2012) for M-Determ and variable neighbourhood search with fast approximations (Hoff et al, 2010) for MStoch1, we expect that similar approaches would also be suitable for M-Stoch2 although M-Stoch2 is much harder due to the additional rerouting variables.…”
Section: Solution Methodologymentioning
confidence: 99%
“…Therefore, it is important that the solution method does not take too long. Bai et al (2010Bai et al ( , 2012 investigated various mechanisms within a guided local search (GLS) framework to reduce the computational time. The experimental study, based on a set of popular benchmark instances, showed that the final algorithm proposed was able to reduce the computational time by one third without worsening the solution quality when compared with Pedersen et al (2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to evaluate the performance of the scheme we propose, experiments have been carried out based on the service network design solutions from Bai et al (2012). Their solutions were obtained as results of experimental tests on a set of benchmark instances for service network design.…”
Section: Computational Results and Analysismentioning
confidence: 99%
“…In contrast to the low-level hybridisation, where one component is a sub-routine of another (see for example [2,20,35]), the high-level relay hybridisation is where both components are self-contained optimisation engines which are executed sequentially -in our matheuristic even iteratively. The hybridisation implemented in our paper differs from the commonly used approach in the high-level hybridisation where an optimisation engine can affect the other components only by providing a starting point in the optimisation search (see for example [14,12,21,23]).…”
Section: Motivation and Comparison With The Existing Literaturementioning
confidence: 99%